PENGARUH PEMBERIAN KALIANDRA (Calliandra calothyrsus) TERHADAP KONSUMSI DAN KECERNAAN NUTRIEN PADA KAMBING BLIGON FASE CEMPE, DARA, DAN INDUK - , FAJRUR ROSYADI, Prof. Dr. Ir. Kustantinah, DEA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the consumption nutrients of diet and digestibility of nutrients in the diet containing Calliandra calothyrsus on Bligon goat: kid, goatling, and doe. Eighteen Bligon goats consists of 6 kids, 6 goatlings, and 6 does were used in this research. Animal of each growth phase were divided into two treatment groups base on feed composition. First treatment, feed consisting of corn forage and the second treatment were fed mixture of 50% corn and 50% Calliandra calothyrsus forage in fresh condition. Examined data were consumption and digestibility of nutrients including dry matter (DM), crude protein (CP), crude fiber (CF), extract ether (EE), non nitrogen free extract (NNFE), and total digestibility nutrients (TDN). Statistic analysis using T - Test analisys with personal computer software Statistical Product and Service Solutions (SPSS) version 15.0. The results showed that the addition of 50% Calliandra calothyrsus in maize forage, increased the consumption of CP and EE in kid, goatling, and doe, but didnât increase the consumption of CF in all phases. Addition of Calliandra calothyrsus increases NNFE consumption only on the kid. The addition of 50% Calliandra calothyrsus in the diet raise CP digestibility coefficients only in kid, but have no effect in goatling and doe, and also significantly did not effect on digestibility coefficients of CF, EE, NNFE, and in kid, goatling, and doe.